A study of appliance ownership and electricity consumption determinants in urban Ghanaian households. (January 2019) - Sakah, Marriette; de la Rue du Can, Stephane; Diawuo, Felix Amankwah; Sedzro, Morkporkpor Delight; Kuhn, Christoph
Highlights: Lighting, air conditioning, refrigeration, television and fan contribute 85% of residential peak load. Household heads aged between 19 and 54 years and in full-time paid employment have high ownership of A.Cs. Appliance ownership, income, household size, floor space and EE awareness & practice explain 57% variance in electricity use. Abstract: The residential sector in Ghana accounts for about 40% of aggregate electricity consumption out of which urban centers contribute 70%. The high weighted share of residential electricity use is attributed to high appliance ownership and use, and other household/building factors. The ability to determine how changes in the pattern of these factors influence electricity demand is critical if efforts to reduce consumption are to be effective. This study combines a residential electricity consumption survey (RECS) with electricity end-use monitoring of 60 households in Tema city Ghana, to yield the first ever comprehensive investigation of city-scale electricity consumption in urban Ghanaian homes. A multiple linear regression analysis is used to identify the most statistically significant indicators of appliance ownership and household electricity consumption. Results indicate that ownership of air conditioner, freezer, fan, refrigerator and television; and changes in socio-economic and building factors such as energy efficiency awareness and practice; income; household size and floor space show high statistical significance, and collectively explain 57% variance in households' total electricity consumption. The presence of dependent children increases ownership of television, iron, washing machine and small kitchen appliances. This work provides a solid foundation for developing more tailored energy-saving policy interventions targeted at households.